2015
DOI: 10.1007/978-1-4939-2584-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cycle Indices from the Photosphere to the Corona: Measurements and Underlying Physics

Abstract: A variety of indices have been proposed in order to represent the many different observables modulated by the solar cycle. Most of these indices are highly correlated with each other owing to their intrinsic link with the solar magnetism and the dominant eleven year cycle, but their variations may differ in fine details, as well as on short-and long-term trends. In this paper we present an overview of the indices that are often employed to describe the many features of the solar cycle, moving from the ones ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…They are also indispensable to reconstructions of past irradiance variations (see, e.g., Solanki et al, 2013). There are various other chromospheric data (Ermolli et al, 2015) that can provide information on plage regions, such as the series of the 10.7 cm radio flux (available since 1947; Tapping and Morton, 2013), Lyman α emission (available since 1969; Woods et al, 2000), Mg II index (available since 1978;Heath and Schlesinger, 1986;Snow et al, 2014), He I (10830Å) equivalent width (since 1977); Ca II (8542Å) central depth (since 1978), Hα central depth (since 1984), CN (3883 Å) bandhead index (since 1979;Livingston et al, 2007), and Ca II K 0.5 or 1 Å disc-integrated emission index (since 1974; White et al, 1998). However, all these measurements cover significantly shorter periods of time and are disc-integrated quantities, carrying less information than the full-disc Ca II K observations.…”
mentioning
confidence: 99%
“…They are also indispensable to reconstructions of past irradiance variations (see, e.g., Solanki et al, 2013). There are various other chromospheric data (Ermolli et al, 2015) that can provide information on plage regions, such as the series of the 10.7 cm radio flux (available since 1947; Tapping and Morton, 2013), Lyman α emission (available since 1969; Woods et al, 2000), Mg II index (available since 1978;Heath and Schlesinger, 1986;Snow et al, 2014), He I (10830Å) equivalent width (since 1977); Ca II (8542Å) central depth (since 1978), Hα central depth (since 1984), CN (3883 Å) bandhead index (since 1979;Livingston et al, 2007), and Ca II K 0.5 or 1 Å disc-integrated emission index (since 1974; White et al, 1998). However, all these measurements cover significantly shorter periods of time and are disc-integrated quantities, carrying less information than the full-disc Ca II K observations.…”
mentioning
confidence: 99%
“…In this regard, several methods were proposed to estimate the optimal embedding dimension m (see e.g. Fredkin & Rice 1995;Rhodes & Morari 1997). In particular, Sello (2001), using the false neighbor method (see for instance Kennel et al 1992;Abarbanel et al 1993), found that the minimum embedding dimension for the sunspot number is m = 5.…”
Section: Methodsmentioning
confidence: 99%
“…Several indices have been introduced in order to represent the many different observables modulated by the solar cycle (Hathaway 2010;Ermolli et al 2014).…”
Section: Data Setmentioning
confidence: 99%
“…However regular high-quality data exist since 1970s (Livingston et al 1976) and thus cover essentially the same period as direct TSI measurements. Besides magnetograms, there are several disc-integrated chromospheric indices (Ermolli et al 2015) that can provide information on facular regions and have been used by various models, such as the 10. Bertello et al 2017).…”
Section: An Overviewmentioning
confidence: 99%